Why Nations Go to War - Stoessinger, John George (GHQ, Rawalpindi Army Education Publishing House, 2003)
Transmitting an understanding of warfare from World War I to the present, WHY NATIONS GO TO WAR, a unique book and a product of reflection by author, John G. Stoessinger, is built around ten case studies, culminating in the new wars that ushered in the twenty-first century: Iraq, Afghanistan, and the wars between Arabs and Israelis in Gaza and in Lebanon. The distinguishing feature of the book remains the author's emphasis on the pivotal role of the personalities of leaders who take their nations, or their following, across the threshold into war.
Include Notes and Selected Bibliography.
WHY NATIONS GO TO WAR is unique. The reflections of author John G. Stoessinger are built around ten case studies and provide a deep analysis of the root causes of modern war, from from World War I to the modern day. The author's main emphasis is on the pivotal role of the personalities of leaders who take their nations, or their following, across the threshold into war. Students are sure to remember Stoessinger's thoughts on war long after their completion of his book. The new 11th edition is completely updated, including references to the recent elections in Afghanistan.
Keywords: History, Modern -- War